2017
DOI: 10.1177/0885328217713631
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of novel meniscal scaffold structures using polyglycolic and poly-l-lactic acids

Abstract: The purpose of this study was to evaluate various types of meniscus scaffolds that mimic the meniscus structure, and to establish a novel cell-free meniscus scaffold with polyglycolic acid or poly-l-lactic acid. Four types of scaffolds were implanted into Japanese white rabbits: poly-l-lactic acid sponge poly-l-lactic acid, PGA-coated PLLA sponge, PGA lamination, and film-coated PGA lamination. Samples were harvested at 8 and 12 weeks after implantation, and a compression stress test was performed. The meniscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
1
18
0
3
Order By: Relevance
“…10,32 We previously evaluated several types of PGA scaffolds for use in meniscal implants and found that PGA covered with polylactic acid/caprolactone, or P(LA/CL), exhibited the highest biomechanical strength and least inflammation in a rabbit model. 20 The purpose of this study was to evaluate meniscal regeneration and prevention of cartilage degeneration as well as the degree of inflammation in a porcine model of meniscal injury.…”
mentioning
confidence: 99%
“…10,32 We previously evaluated several types of PGA scaffolds for use in meniscal implants and found that PGA covered with polylactic acid/caprolactone, or P(LA/CL), exhibited the highest biomechanical strength and least inflammation in a rabbit model. 20 The purpose of this study was to evaluate meniscal regeneration and prevention of cartilage degeneration as well as the degree of inflammation in a porcine model of meniscal injury.…”
mentioning
confidence: 99%
“…Outro aspecto importante é que o arcabouço deve possuir funções biomecânicas que atenderão as necessidades do paciente (16,17,50). Isto deve ocorrer até o fim do processo de regeneração tissular(3).…”
Section: Resultsunclassified
“…Por envolver testes em seres vivos, as análises in vivo devem estar de acordo com protocolos de ética estabelecidos pelas instituições de pesquisa. As publicações analisadas escolheram em sua grande maioria modelos de animais pequenos, como coelhos (1,17,49,50,58,59) e camundongo (19). DEPONTI et al (2013)(2) concluem que do ponto de vista anatômico o menisco caprino é o mais semelhante ao humano e que outros modelos interessantes são os suíno e os ovinos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Although PLLA can be degraded and has certain supporting performance, its supporting performance is still poor than that of metal scaffolds due to its own limitations. Simultaneously, the lactic acid metabolites produced during the degradation of the PLLA composite will cause long-term chronic stimulation to the vascular tissues around the scaffold, which will induce and aggravate the inflammatory reaction and delay the healing of blood vessels [5,6]. In addition, increasingly more advanced thrombus formation and stent restenosis are more challenging for single PLLA scaffold in clinical trials.…”
Section: Introductionmentioning
confidence: 99%